OPPRESSION AND RACISM TOWARD BLACK AMERICAN IN “12 YEARS A SLAVE” MOVIE - Swi Idayati Simanjuntak; Sri Minda Murni (State University of Medan, 2015)
The study deals with those oppressions faced by Black American in “12 Years aSlave” movie and what resistances they showed toward those oppressions. Theobjectives of the study are to describe the oppressions faced by the two maincharacters – Platt and Patsey and to explain the resistances they shown in “12Years a Slave” Movie. This research focuses the study merely on oppressionfaced by two main characters; they were Salomon Northup or Platt and Patsey.This research was conducted by using descriptive qualitative design and limitedon two of main characters. The data analysis result was found five kinds ofoppression faced by black American in this film, those were: powerlessness,exploitation, marginalization, culture imperialism and violence. The resistancesshown by American toward those oppressions were revolt, radicalism, asking forhelp and religion or spirituality. The issue of racism with oppression had been thecrucial issue since long time ago which could not be denied that until nowadaysthe issue of racism is still happening though without oppression. The stigma ofBlack was being inferior and white was being superior had driven mind into thedestruction of race relationship between Black and White. However, in this filmwe could see how badly the oppression faced by black American and how theystruggled for fighting toward those oppressions.